RESPON BIBIT BUD SETT TEBU PADA PERKECAMBAHAN DAN PERTUMBUHAN TERHADAP PERLAKUAN LAMA PENYIMPANAN DAN PERENDAMAN ZPT SEBELUM TANAM - Umi Kusumastuti Rusmarini; Yohana Theresia Maria Astuti; Barkah Imam Santoso (AGROISTA : Jurnal Agroteknologi, 2022)
Sugarcane problems in germination will effect on growth and the yield that is not optimal. The solution obtained from these problems is plant growth regulators soaking and storage time bud sett seedling before planting. This study used a factorial experimental method with the first factor being storage time consisting of 3 levels, namely 0 days (control), 1 day, and 2 days. The second factor was PGR soaking which consisted of control (without PGR soaking), NAA + IBA, and IAA . The experiment was carried out in a completely randomized design with 3 replications. The results of the observations were analyzed by means of variance at the 5% level and the DMRT test to determine the differences between treatments. The combination of storage time and soaking PGR treatments affected the germination of sugarcane seedlings. Control treatment, NAA+IBA , IAA soaking and 1-day storage,germinated faster than the same treatment and stored for 2 days, even seedling soaked in PGR did not germinate. The NAA+IBA, IAA soaking treatment and 1 day storage had better growth than the same treatment, without storage and 2 days storage.The length of storage and soaking of several PGRs before planting gave the same effect on the age of shoots and the number of shoots. Key words : Sugarcane bud sett, plant growth regulators soaking, storage time, IAA,IBA, NAA